2018
DOI: 10.1186/s12884-018-1953-4
|View full text |Cite
|
Sign up to set email alerts
|

Understanding health systems to improve community and facility level newborn care among displaced populations in South Sudan: a mixed methods case study

Abstract: BackgroundTargeted clinical interventions have been associated with a decreased risk of neonatal morbidity and mortality. In conflict-affected countries such as South Sudan, however, implementation of lifesaving interventions face barriers and facilitators that are not well understood. We aimed to describe the factors that influence implementation of a package of facility- and community-based neonatal interventions in four displaced person camps in South Sudan using a health systems framework.MethodsWe used a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 31 publications
1
71
0
Order By: Relevance
“…The low use of family planning services was found to be influenced by social and cultural norms [28,29,38]. A study conducted in Renk County based on a participatory ethnographic approach indicated that the participants experienced pressure to increase the size of their families.…”
Section: Health System Gaps Service Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…The low use of family planning services was found to be influenced by social and cultural norms [28,29,38]. A study conducted in Renk County based on a participatory ethnographic approach indicated that the participants experienced pressure to increase the size of their families.…”
Section: Health System Gaps Service Deliverymentioning
confidence: 99%
“…Low motivation Only two studies reported data on healthcare providers' motivation [38,53]. A qualitative study conducted in Juba with 18 healthcare providers reported poor supervision, a lack of training opportunities, and low salary to be the determinants influencing the motivation of healthcare providers and thus affecting their performance [53].…”
Section: Health Workforcementioning
confidence: 99%
“…At the global level, learnings were used beyond humanitarian settings to inform methodologies for measuring newborn care signal functions in other low resource settings and a newborn medical supply kit for community-and facility-based care. (18,19) The ndings of this research have been shared through the Newborn Health in Emergencies webpage hosted by Save the Children, (20) blogs disseminated through the Healthy Newborn Network, (20-22) a correspondence published in The Lancet,(23) a public webinar as part of Save the Children's Health and Nutrition Series, (24) poster and oral presentations at several international conferences, and research articles in peer-reviewed journals (9)(10)(11). Several policy and programmatic changes were also made at the global level such as development of a global roadmap to accelerate newborn health program scale-up in humanitarian settings and the Newborn Health Humanitarian Settings Field Guide that included an implementation toolkit.…”
Section: Background Humanitarian Contextmentioning
confidence: 99%
“…Improvements in knowledge, however, did not lead to adoption of interventions at the community level. Postnatal home visits in the rst week of life, while new and acceptable to community health workers, were not sustained during periods of mass displacement because of the inability to locate households and limited staff available to manage competing priorities (11). In facilities, partograph use for fetal monitoring, skin-to-skin contact, and postnatal monitoring of danger signs were the least commonly used practices at baseline, highlighting gaps in care for small and sick newborns.…”
mentioning
confidence: 99%
“…(10) Improvements in knowledge, however, did not lead to adoption of interventions at the community level. Postnatal home visits in the first week of life, while new and acceptable to community health workers (CHWs), were not sustained during periods of mass displacement because of the inability to locate households and limited staff available to manage competing priorities (11). At the facility level, partograph use for fetal monitoring, skin-to-skin contact, and postnatal monitoring of danger signs were the least commonly used practices at baseline, highlighting gaps in care for small and sick newborns (9).…”
mentioning
confidence: 99%